Collagenous matrix as a predictor for bone formation: a digital technique for collagen quantification (Revista da Faculdade de Odontologia - UPF, 2017)
The collagenous matrix plays a fundamental role in the process of bone regeneration, so it is essential to studyhow it is primarily formed in situations in which critical bone defects are created. Objective: this study seeksto quantify the collagenous matrix formed in critical bone defects in the calvaria of mice over the processof bone regeneration promoted by the association of poly(lactide-co-glycolide) (PLGA) porous scaffolds andstem cells from deciduous teeth (SCDT). In addition, this study attempted to establish a precise protocol forthe digital quantification of collagen through a histological method. Materials and method: Nine Wistar ratswere used, in which critical defects of 8.0 mm of diameter were made in their calvarium. The animals weredivided into three groups (n = 9): I – PLGA scaffolds; II – PLGA scaffolds/SCDT; III – PLGA scaffolds/SCDTmaintained in osteogenic medium for 13 days. Within sixty postoperative days, calvaria were removed for histometric analysis following a digital protocol. A specific digital analysis method was designed for this study, inwhich a more precise quantification and differentiation between collagen fibers and non-collagenous tissuewas possible, excluding factors that would normally alter the results. Results: it was noted that the associationof PLGA scaffolds and SCDT maintained in osteogenic medium resulted in collagen matrix formation statisticallyhigher than the other groups (p